The 30th International Conference on Plasma Science, 2003. ICOPS 2003. IEEE Conference Record - Abstracts.
DOI: 10.1109/plasma.2003.1230030
|View full text |Cite
|
Sign up to set email alerts
|

Cathode erosion mechanisms in an oxygen plasma cutting arc

Abstract: Plasma surfacing is'an important enabling technology in highperformance coating applications. Recently, it is being applied to rapid prototyping/tooling to reduce development time and manufacturing cost for the development of new product. In this technology, a plasma arc beam is used as thermal energy source, metal powders are preheated in plasma arc and deposited in melt pool on the hase plate or deposited layer synchonously, with the move ment of plasma gun and/or worktable controlled by CNC according to CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…For a given torch design, arc current, plasma gas and gas flow rate, the final distribution of the potential inside the torch is obtained self-consistently with the realized plasma resistivity and the corresponding current distribution. In the plot of voltage drop along the central axis (figure 17), the total voltage drop across the segment of the arc is found to be 64 V, a value, close to the 67 ± 4 V, realized experimentally [39].…”
Section: Current Density and Potential Distributionsupporting
confidence: 73%
“…For a given torch design, arc current, plasma gas and gas flow rate, the final distribution of the potential inside the torch is obtained self-consistently with the realized plasma resistivity and the corresponding current distribution. In the plot of voltage drop along the central axis (figure 17), the total voltage drop across the segment of the arc is found to be 64 V, a value, close to the 67 ± 4 V, realized experimentally [39].…”
Section: Current Density and Potential Distributionsupporting
confidence: 73%
“…This type of erosion dominates when cutting small parts. In spite of the obvious importance of this phenomenon in practice, only a little attention was paid to this problem in the scientific literature [2,3]. One of the most important questions regarding CE is when this erosion occurs: does it occur during the arc start (on-erosion) or during the arc termination (off-erosion)?…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important questions regarding CE is when this erosion occurs: does it occur during the arc start (on-erosion) or during the arc termination (off-erosion)? In the report [2], it has been shown that either type of cycling erosion may dominate depending on how fast the arc current goes down: off-erosion prevails when the arc current is shut down fast and vice versa. Also, it has been shown in this report that the cathode erodes in the form of particles (agglomerates); small agglomerates during the on-erosion and relatively large agglomerates during the off-erosion.…”
Section: Introductionmentioning
confidence: 99%
“…LGF construction. In order to analyse the light intensity signal in terms of symmetry, a LGF, one of the wavelet transform functions, is applied to the light intensity signal [26]. Figure 13 shows two examples of LGFs in the frequency domain according to the different centre frequencies, w 0 , which will be discussed later.…”
Section: Analysis Of Schlieren Imagesmentioning
confidence: 99%
“…By changing the centre frequency (w 0 ), the filters cover different local frequency regions where the filter gives high weighting factors (figure 13). Each value of w 0 is designed to pick out a particular band of frequencies from the signal being analysed [26]. By performing the inverse FFT (IFFT) on the above filters even and odd responses of the log-Gabor wavelets in the physical domain (not in the frequency domain) are obtained as shown in figure 14, at the different centre frequencies, respectively.…”
Section: Analysis Of Schlieren Imagesmentioning
confidence: 99%